The Impact of Validity Screening on Associations Between Self-Reports of Bullying Victimization and Student Outcomes. (February 2018) - Jia, Yuane; Konold, Timothy R.; Cornell, Dewey; Huang, Francis
Self-report surveys are widely used to measure adolescent risk behavior and academic adjustment, with results having an impact on national policy, assessment of school quality, and evaluation of school interventions. However, data obtained from self-reports can be distorted when adolescents intentionally provide inaccurate or careless responses. The current study illustrates the problem of invalid respondents in a sample ( N = 52, 012) from 323 high schools that responded to a statewide assessment of school climate. Two approaches for identifying invalid respondents were applied, and contrasts between the valid and invalid responses revealed differences in means, prevalence rates of student adjustment, and associations among reports of bullying victimization and student adjustment outcomes. The results lend additional support for the need to screen for invalid responders in adolescent samples.